Mechanistic insights into diatom iron uptake: In vitro siderophore characterization and in silico modelling and docking of ISIPs in iron-limiting conditions - Pratika Singh; Rantim Bhattacharjee; Parli Venkateswaran Bhaskar; Vitthal T. Barvkar; Anand Jain; Sarat Chandra Tripathy; Rahul Mohan (Marine Environmental Research, 2026)

Deep-water nutrients mediated glacial-interglacial diatom productivity in the Indian Polar Front Zone of the Southern Ocean - Aditi Nautiyal; Sunil Kumar Shukla; Rahul Mohan (Marine Micropaleontology, 2026)

Astrocyte-microglia crosstalk in Lead-induced neurotoxicity: Molecular signaling and downstream pathological sequelae - Suman Maity; Moumita Saha; Zahwa Fathima; Yoshitha Kondeti; Rahul L. Gajbhiye; Mohan Gandhi Bonthu; Shriram D. Ranade; Sudheer Moorkoth; Srinivas Mutalik; Ramalingam Peraman; Pothuraju Naresh (Chemico-Biological Interactions, 2026)

Immunomodulatory and locomotor regulations via Diosgenin treatment in lipopolysaccharide-induced chronic fatigue syndrome (CFS)/ depressive despair symptom: an in vivo assessment - Rahul Lotan Shirole; Mohan Rajendra Khalane; Vijayeta Pralhad Nage; Nitin Lotan Shirole; Sushil Vilas Chawre; Abdulrhman Alsayari; Shadma Wahab; Adrija Bhunia; Digvijay Kailas Patil (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Interannual dynamics of plankton communities and carbon biomass across Southern Ocean frontal systems - Athirpankandi Sreerag; Rajani Kanta Mishra; Vankara Venkataramana; Melena Augusta Soares; Rahul Mohan (Limnology and Oceanography, 2026)
The Indian Sector of the Southern Ocean (ISSO) is a key region for global biogeochemical cycling, where strong frontal systems regulate nutrient supply and ecosystem structure. During two austral summer expeditions (2018 and 2020), we examined phytoplankton and zooplankton communities across the Subtropical Front (STF), Subantarctic Front (SAF), Polar Front (PF), and south of the Polar Front (SPF) using hydrography, nutrients, HPLC–CHEMTAX pigments, microscopic cell counts, taxon‐resolved carbon biomass, and zooplankton abundances. Environmental gradients were pronounced: STF surface waters were warm (12–16°C) and saline (~ 35), with low nitrate and silicate, whereas PF/SPF waters were cooler (0–3°C), fresher, and nutrient‐rich, with silicate up to 49 μ M. These gradients structured phytoplankton composition: cryptophytes contributed 40–50% of chlorophyll‐ a in STF, while dinoflagellates ( Gyrodinium sp.) reached ~ 1400 cells L −1 , contributing ~ 1.0 μ g C L −1 . Polar Front and SPF were dominated by diatoms ( Fragilariopsis sp., Chaetoceros sp., Thalassiosira sp.), contributing 45–55% of chlorophyll‐ a and up to 1.7 μ g C L −1 . Zooplankton co‐varied with phytoplankton, with calanoid copepods increasing from ~ 110 ind. m −3 in PF (2018) to ~ 756 ind. m −3 in 2020, coinciding with higher diatom biomass in the same frontal zones. Correlations confirmed associations, with cryptophytes positively linked to temperature and negatively to nitrate and silicate, while diatoms were associated with cooler, nutrient‐rich waters. These findings show that gradients in temperature, salinity, and nutrients structure phytoplankton composition and carbon biomass, which in turn co‐vary with zooplankton. This study provides a quantitative assessment of interannual variability in the ISSO and highlights the critical role of frontal systems in modulating Southern Ocean carbon cycling.

Response of zooplankton to unusual increase in temperature and sea ice melting in a changing environment (Prydz Bay), coastal Antarctica: Climate change perspective - V. Venkataramana; R.K. Mishra; Melena A. Soares; P. Sabu; Alvarinho J. Luis; A. Sarkar; T. Jabir; A.Srinivas Rao; Rahul Mohan (Progress in Oceanography, 2026)

Urdamycin V from Streptomyces sp induces p53 independent apoptosis in cervical cancer cells inconsiderate of HPV status and inhibited growth of gram-positive human pathogens - Vipin Mohan Dan; Rahul Sanawar; Gama M. G. Mohan; Soniya P. Cheriyan; Thankayyan R. Santhosh Kumar (Natural Product Research, 2025)

Late Holocene paleoceanography of the Knipovich Ridge area (Norwegian Sea) based on micropaleontological data - Tatiana S. Klyuvitkina; Ekaterina A. Novichkova; Elizaveta A. Agafonova; Lubov A. Lozinskaia; Karina S. Iakimova; Alexander G. Matul; Maria P. Chekhovskaya; Rahul Mohan; Anne de Vernal (Marine Micropaleontology, 2025)

Recurring eddies in the Southern Subtropical and Subantarctic Frontal regions of the Indian sector of the Southern Ocean during austral summer - P. Sabu; S. Cxynna; N.N.S. Vishnu; Nirmala J. Nair; Jenson V. George; N. Anilkumar; Rahul Mohan (Dynamics of Atmospheres and Oceans, 2025)

Landslide hazard assessment in parts of upper Bhagirathi Basin: a comparative study using earth observation and machine learning based initiatives in perspective of slope instability - P Danuta Mohan; Rahul Das; Shovan Lal Chattoraj; Yateesh Ketholia (Bulletin of Engineering Geology and the Environment, 2025)

First report of wild roses as natural hosts of apple stem grooving virus in India - Pooja Bhardwaj; Rahul Mohan Singh; Devendra Dhyani; Vipin Hallan (Journal of Plant Pathology, 2025)

Three-component models for the detection of phytoplankton size classes in the Indian sector of the Southern Ocean: Insights into climate-driven community shifts - Sudarsana Rao Pandi; Sarat Chandra Tripathy; Carlos Rafael B. Mendes; R. Chandrasekhar Naik; Sunil Kumar Padhi; Aneesh A. Lotliker; Rahul Mohan (Journal of Marine Systems, 2025)

The role of atmospheric and oceanic factors on the record low Antarctic sea ice extent of 2023 - M. Swathi; Avinash Kumar; Juhi Yadav; Rahul Mohan (Global and Planetary Change, 2025)

Environmental magnetism linked to weathering processes: A study on surface soils from an East Antarctic oasis - Adyasha Rath; G.S. Joju; Anish Kumar Warrier; Marcos A.E. Chaparro; Firoz Badesab; Mamilla Venkateshwarlu; B.S. Mahesh; Rahul Mohan (Geoderma Regional, 2025)

Trends in Antarctic Sea Ice and Albedo: Impacts of Ocean‐Atmospheric Processes - M Swathi; Aakriti Srivastava; Avinash Kumar; Juhi Yadav; Dinesh Chandra Gupta; Rahul Mohan (International Journal of Climatology, 2025)
Surface albedo (SAL), a critical factor in climate studies, significantly impacts the Earth's radiation budget and sea ice dynamics. The long‐term spatial and temporal variability of Antarctic SAL were derived from the third edition of the Cloud, Albedo, and Surface Radiation Dataset (CLARA‐A3). The analysis focused on spring and summer across five longitudinal sectors around Antarctica. The relationships of sea ice concentration (SIC) and SAL with climatic variables such as sea surface temperature (SST), 2 m air temperature (T2m), turbulent heat flux, and total cloud cover are explored in detail. The study examined SAL changes in two distinct timescales, pre‐2015 (1979–2015) and post‐2015 (2016–2021), to understand sea ice variations and trends in Antarctic climate change. The study revealed contrasting summer SAL trends, with a positive trend pre‐2015 and a decreasing trend post‐2016 across most of Antarctica, except the Amundsen‐Bellingshausen Sea, which showed an opposite trend. West Antarctica exhibited higher SAL compared to East Antarctica. SAL and SIC were significantly negatively correlated with SST, T2m, and turbulent heat flux across all sectors. Cross‐seasonal lead–lag analysis indicated that increased turbulent heat flux was followed by an increase in SAL after 1–5 months. Wind patterns showed that winds from higher to lower latitudes increased SIC and SAL, while winds from lower to higher latitudes reduced SIC. Post‐2015, notable wind direction reversals were observed in the Antarctic Peninsula during spring. Sectors with higher cloud cover absorbed more ocean heat, reducing turbulent heat flux and affecting SAL. Overall, post‐2015 observations highlighted major shifts in sea ice dynamics and SAL trends during both spring and summer seasons. The SIC decreased markedly across all sectors, with the Weddell Sea showing the most significant reduction. This study highlights regional and seasonal variations in SAL and its interactions with SIC and climatic factors, emphasising shifts in trends post‐2015.

Ocean surface conditions during Holocene Thermal Maximum in Kongsfjorden, Svalbard, and its relevance for understanding modern warming in the region - Harikrishnan Guruvayoorappan; Dmitry V. Divine; Arto Miettinen; Rahul Mohan; Katrine Husum; Syed Mohammad Saalim; Lisa Claire Orme (Quaternary Science Reviews, 2025)

Characterising cowpea (Vigna unguiculata L. Walp) mini-core set for flowering responses to various photoperiod and temperature regimes - T. Lakshmi Pathy; A. Mohan Rao; T. V. Krishna; Kuldeep Tripathi; S. Ramesh; N. Akshay Rahul; Akshata G. Bhat; Pratibha B. Honnannavar (Genetic Resources and Crop Evolution, 2025)

Phytoplankton dynamics in the Antarctic marginal ice zone: Trends and drivers - Prince Prakash; Rahul Mohan; Ravidas K. Naik; Alvarinho J. Luis (Journal of Marine Systems, 2025)

Spatial distribution of picoeukaryotic community from the hydrographic fronts of the indian sector of the southern ocean as revealed by metabarcoding - Tushar Kaushik; Vaishnavi Dixit; Rahul Mohan (Polar Biology, 2025)

Advanced environmental remediation using enhanced performance of hollow ZnO@SnIn4S8 core-shell nanorod arrays for hazardous ion and organic pollutant removal - Mohan Reddy Pallavolu; Vanish Kumar; Rahul Ranjan; Sanjeev Kumar; Adem Sreedhar; Mrinmoy Misra (Journal of Environmental Management, 2025)

Enhancing the silica-magnetic catalyst-assisted bioethanol production from biowaste via ultrasonics - Hemalatha Manivannan; Anikesh Krishnamurthy; Rahul Macherlla; Siva Chidambaram; Saravanan Pandiaraj; Muthumareeswaran Muthuramamoorthy; Selvarajan Ethiraj; G. Mohan Kumar (Clean Technologies and Environmental Policy, 2024)

Source, bioavailability, and toxicity of metals in modern fjord sediments, west Spitsbergen, and their influence on sediment-associated biota - Shabnam Choudhary; Saalim Syed Mohammad; Rahul Mohan; Manish Tiwari (Frontiers in Marine Science, 2024)
Metal contamination in the Arctic region has increased over the years despite its remote and isolated location. Thus, to evaluate the bioavailable fractions of various metals and their effects on sediment-associated biota, the surface sediments from the fjords were analyzed for bulk concentration of metals and their speciation in different fractions. Metals concentrations were higher in the inner fjord region and decreased towards the outer fjord, supported by the terrigenous influence (TI%) calculated. Cr and Pb showed higher excess values attributed to their additional source other than the catchment rocks. So, to assess the metal-related ecological risk, the bulk concentration of metals was compared with Arctic sediment quality guidelines (ASQGs). Cr, Cd, and Pb concentrations were high, indicating potential adverse biological effects in the study. To avoid the risk of overestimation, metal speciation was conducted, showing that overall metal concentrations were higher in the residual fraction; however, higher concentrations of Mn in labile phases pose a moderate risk to the sediment-associated biota. Additionally, the population density of foraminifera in the sediments was calculated to assess the influence of bioavailable metal on benthic foraminifera. It was found that the presence of metals in bioavailable fractions affected the abundance of the foraminifera. However, no morphological abnormalities were observed in the species.

Contrasting response of regional spring Arctic Sea ice variations on Indian summer monsoon rainfall - Juhi Yadav; Avinash Kumar; Seong-Joong Kim; Rohit Srivastava; Rahul Mohan; M. Ravichandran (Remote Sensing of Environment, 2024)

Short-term time-series observations of phytoplankton light-absorption and productivity in Prydz Bay, coastal Antarctica - Sarat C. Tripathy; Anvita U. Kerkar; P. Sabu; Sunil K. Padhi; Sudarsana R. Pandi; Amit Sarkar; Bhaskar V. Parli; Rahul Mohan (Frontiers in Marine Science, 2024)
The optical characteristics of coastal Antarctic waters exhibit complexity due to the dynamic hydrography influenced by meltwater intrusion, which alters nutrient levels, thermohaline structure, and optically active substances (OAS) regimes. Studies on bio-optical variability and its implications on phytoplankton productivity (PP) are scanty in coastal polar regions. On this backdrop, time-series measurements (72 h at 6 h intervals) of bio-optical properties such as phytoplankton biomass (chlorophyll-a), absorption (a ph ), and total suspended matter (TSM) concurrently with PP were measured to understand their interplay and variability in relation to the ambient physicochemical settings in the under-sampled Prydz Bay, coastal Antarctica. Our findings revealed thermohaline stratification within the bay, likely attributed to the inflow of less saline meltwater from nearby glaciers and minimal wind activity. The consistent presence of sub-surface chlorophyll maximum (SCM) beneath the stratified layer underscored the light-acclimatization response of shade-adapted phytoplankton. Surface waters exhibited higher TSM compared to deeper layers, indicating glacial melt influence, while the depth of the sunlit layer remained relatively stable, suggesting limited water mass movement and/or variability in OAS at the study site. An inverse relation between chlorophyll-a and chlorophyll-a-specific phytoplankton light absorption (a* ph (λ)) manifested ‘pigment package effect’ within the prevailing phytoplankton community, implying reduced light-absorption efficiency and consequent lower PP. Compared to chlorophyll-a, the phytoplankton light absorption (a ph (λ)) emerged as a better proxy for explaining PP variability. Nutrient availability was not limiting, which was conducive to micro (large) phytoplankton growth. Classification of phytoplankton size classes (micro, nano, and pico) based on the B/R ratio (a ph at Blue (443 nm)/Red (676 nm) region) confirmed the dominance of larger (micro) phytoplankton that are more susceptible to package effect, thus have implications on reduced PP potential of this polar marine ecosystem.

Editorial: Research advances from Larsemann Hills, Antarctica: International cooperation and future prospects (Part-2) - Anand K. Singh; Shailendra Saini; Yogesh Ray; Svetlana Grigoreva; Xiangbin Cui; Xianglan Li; Rahul Mohan; M. Javed Beg; Rasik Ravindra (Polar Science, 2024)

Finding identical sequence repeats in multiple protein sequences: An algorithm - Vikas Kumar Maurya; Madhumathi Sanjeevi; Chandrasekar Narayanan Rahul; Ajitha Mohan; Dhanalakshmi Ramachandran; Rashmi Siddalingappa; Roshan Rauniyar; Sekar Kanagaraj (Journal of Biosciences, 2024)

Concurrent reduction of the fume and Cr (VI) concentrations of inhalable and respirable particle using a new covered stainless-steel SMAW electrode - M. Rahul; S.P. Sivapirakasam; Mohan Sreejith; B.R. Vishnu; Krishna Vijayakumar (Journal of Environmental Chemical Engineering, 2024)

Morphological changes and future projections of the Getz Ice shelf, western Antarctica—A statistical and geospatial approach - Aakriti Srivastava; Avinash Kumar; Juhi Yadav; Dinesh Chandra Gupta; Rahul Mohan (Regional Studies in Marine Science, 2023)

Editorial: Research advances from Larsemann Hills, Antarctica: International cooperation and future prospects - Anand K. Singh; Shailendra Saini; Yogesh Ray; Svetlana Grigoreva; Xiangbin Cui; Xianglan Li; Rahul Mohan; M. Javed Beg; Rasik Ravindra (Polar Science, 2023)

International collaboration- An indispensable tool for Antarctic research: Status report of India's endeavours on the icy continent - Swati Nagar; Yogesh Ray; Rakesh Rao; Avinash Kumar; Rahul Mohan (Polar Science, 2023)

High-resolution insights of physical properties of water columns of lakes at the Larsemann Hills, East Antarctica - Cheryl A. Noronha-D’Mello; B.S. Mahesh; Jenson George; Shramik Patil; Avirajsinh Jadav; Rahul Mohan (Polar Science, 2023)

Mineral magnetic properties of surface soils from the Broknes and Grovnes Peninsula, Larsemann Hills, East Antarctica - G.S. Joju; Anish Kumar Warrier; Marcos A.E. Chaparro; B.S. Mahesh; Freddy Abraham Matthew; S. Anusree; Rahul Mohan (Polar Science, 2023)

Latent heat flux variability over the tropical Indian Ocean - Soumya Mohan; R. D. Ruchith; S. Rahul; P. R. Shanas (International Journal of Climatology, 2023)
The seasonal evolution and interannual variability of latent heat flux (LHF) over the tropical Indian Ocean (TIO) region is examined for the period 1980–2019. The seasonal distribution of LHF is dominated by the winter pattern of each hemisphere in the TIO. Climatologically high LHF is mostly confined to the Arabian Sea and Bay of Bengal regions in the north Indian Ocean and the zonal belt between 10 o S and 25 o S in the south Indian Ocean. Warm and cold phases of El‐Niño Southern Oscillation, Indian Ocean Dipole (IOD), and their co‐occurrence events leave distinct LHF signatures over the TIO. The LHF anomalies during these events are more profound than pure events with enhanced latent heat loss when the La Niña and negative IOD events coincide. The LHF anomalies associated with the wind‐evaporation‐SST feedback is prominent when positive IOD co‐occur with the El‐Niño event. Both the vertical humidity gradient and wind speed changes play substantial roles in driving LHF anomalies during the co‐occurring events of NIOD and La Niña.

Study on the soluble and insoluble fume and hexavalent chromium emitted from a new covered electrode with micro and nano sized-sodium and potassium titanate–based flux - Rahul Madhusoodhanan; Sivapirakasam Suthangathan Paramashivan; Sreejith Mohan; Vishnu B. Rajeshwari (Environmental Science and Pollution Research, 2023)

Molecular evidence of Apple Stem Grooving Virus infecting Pear in India - Pooja Bhardwaj; Rahul Mohan Singh; Vipin Hallan (Indian Phytopathology, 2023)

Delineation of thin and discrete sand reservoir facies from shale-dominated Kopili Formation (Middle to Late Eocene) using the post-stack seismic inversion and neural network algorithm: A case study from Assam Basin, India - Satya Narayan; Rahul Singh; Anand Mohan; Kumar Vivek; Paridhi Acharya; S K Pal (Journal of Earth System Science, 2023)

Spatiotemporal evolution of sea ice and its teleconnections with large-scale climate indices over Antarctica - M. Swathi; Avinash Kumar; Rahul Mohan (Marine Pollution Bulletin, 2023)

Variations in the Southern Ocean carbonate production, preservation, and hydrography for the past 41, 500 years: Evidence from coccolith and CaCO3 records - Pallavi Choudhari; Abhilash Nair; Rahul Mohan; Shramik Patil (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Malformation in coccolithophores in low pH waters: evidences from the eastern Arabian Sea - Suhas Shetye; Sahina Gazi; Arundhathy Manglavil; Damodar Shenoy; Siby Kurian; Anil Pratihary; Gayatri Shirodkar; Rahul Mohan; Albertina Dias; Hema Naik; Mangesh Gauns; Kuniyil Nandakumar; et al. (Environmental Science and Pollution Research, 2023)

Generative models for age, race/ethnicity, and disease state dependence of physiological determinants of drug dosing - Rahul Nair; Deen Dayal Mohan; Srirangaraj Setlur; Venugopal Govindaraju; Murali Ramanathan (Journal of Pharmacokinetics and Pharmacodynamics, 2022)

SARS-CoV-2-associated haemorrhagic encephalitis mimicking Herpes encephalitis - Rahul Handa; Satyan Nanda; Atul Prasad; Rajiv Anand; Man Mohan Mehndiratta; Dhruv Zutshi; Aarti Pahuja; Rajesh Kumar Pandey; Payal Mittal; Sachal Sharma; Sujata K Dass; Prabhjeet Kaur Bedi; et al. (Journal of NeuroVirology, 2022)

Planktic Foraminiferal Assemblages in Surface Sediments From the Subpolar North Atlantic Ocean - Nibedita Sahoo; Syed Mohammad Saalim; Alexander Matul; Rahul Mohan; Anna Tikhonova; Nina Kozina (Frontiers in Marine Science, 2022)
The subpolar North Atlantic (SPNA) Ocean has complex hydrography, and moderates the global climate through the Atlantic Meridional Overturning Circulation (AMOC). The surface water mass dynamics in SPNA and the upper limb of AMOC, govern the plankton distribution. Specifically, the habitat of modern planktic foraminifera is strongly affected by the SPNA hydrography. In the present study, 25 surface sediment samples from the Labrador Sea to the Iceland-Faroe-Shetland Channel (IFSC) were examined for planktic foraminifera distribution along a latitudinal transect at 59.50°N. The planktic foraminifera distribution followed the transition in water mass structure in the study area from the Sub-Arctic water in the west to the warm North Atlantic water in the east. Temperature and salinity are two dominant ecological factors controlling planktic foraminifera assemblages in the region. This hydrographic contrast was also reflected in the ratio of Neogloboquadrina pachyderma / Neogloboquadrina incompta along the transect. Based on the cluster analysis, the planktic foraminifera assemblages could be assigned to three groups. A cold/polar group in the Labrador Sea, a mixed (both cold and warm) group in the Irminger Sea and IFSC, and a warmer temperate group in the eastern part of the transect were represented by different planktic foraminifera assemblages. Additionally, a decrease in Globorotalia inflata in the eastern transect and an increase in Turborotalita quinqueloba in the Iceland basin and Irminger Sea was observed in our study when compared with the published dataset. From this, we suggest a shift in planktic assemblages in the SPNA. The present study on the distribution of modern planktic foraminifera can help paleoceanographic reconstructions in the SPNA ocean.

Magnetic properties of surface sediments in Schirmacher Oasis, East Antarctica: spatial distribution and controlling factors - Anish Kumar Warrier; Joju George Sebastian; K. Amrutha; A. S. Yamuna Sali; B. S. Mahesh; Rahul Mohan (Journal of Soils and Sediments, 2021)
Purpose We investigated the magnetic properties (abundance, grain size, and mineralogy) of iron oxides present in Lake L-55 sediments, Schirmacher Oasis, East Antarctica, with an aim to understand their spatial distribution and the underlying mechanisms that control their formation and distribution. Methods Twenty-five surficial sediments retrieved from different parts of Lake L-55 were subjected to the entire range of environmental magnetic (magnetic susceptibility, anhysteretic remanent magnetization (ARM), isothermal remanent magnetization (IRM)) measurements (at different field strengths). Inter-parametric ratios ( χ ARM /SIRM, χ ARM / χ lf , χ ARM / χ fd , IRM 20 mT /SIRM, IRM 20 mT /ARM, S -ratio, L -ratio) provided insights into the magnetic properties (abundance, grain size, and mineralogy of iron oxides). Scanning electron microscopic-energy dispersive X-ray spectroscopic (SEM-EDS) analysis was performed on magnetic extracts from a few sediments. Besides, organic matter (%) was also calculated for the sediment samples. Principal component analysis was performed to gain information on the presence of different components and their relative dominance. Results The iron oxides are strongly magnetic (high values of concentration-dependent parameters). The principal iron oxide is magnetite ( S -ratio > 0.90) which is coarse-grained (multi-domain (MD) and stable single-domain (SSD) grains), and there is no influence of authigenic greigite, bacterial magnetite, and anthropogenic magnetite. The mineralogy is confirmed by SEM-EDS data. The iron oxides are of different grain sizes, and their contribution is in the order of MD > SSD > SP as shown by the principal component analysis. Pedogenic iron oxide minerals seem to be present in the samples whose formation is due to the oxidation of magnetite into hematite. However, they are of SSD size and not SP, suggesting that the intensity of pedogenesis is not sufficient to form SP grains. Conclusion The iron oxide minerals are mainly terrigenous, and the biogenic activity within the lake is not sufficient to modify the ferrimagnetic minerals. Spatial distribution patterns suggest the non-uniform distribution of magnetite/titanomagnetite of varying sizes in the lake basin which is transported by both melt water streams and winds.

Vertical distributions of the microscopic morphological characteristics and elemental composition of aerosols over India - Mukunda M. Gogoi; Roseline C. Thakur; Sahina Gazi; Vijayakumar S. Nair; Rahul Mohan; S. Suresh Babu (Journal of Atmospheric Chemistry, 2020)

Dramatic decline of Arctic sea ice linked to global warming - Juhi Yadav; Avinash Kumar; Rahul Mohan (Natural Hazards, 2020)

Distribution of Polycystine Radiolarians in Bottom Surface Sediments and Its Relation to Summer Sea Temperature in the High-Latitude North Atlantic - Alexander Matul; Rahul Mohan (Frontiers in Marine Science, 2017)

Response of Sandy Lake in Schirmacher Oasis, East Antarctica to the glacial-interglacial climate shift - Badanal Siddaiah Mahesh; Anish Kumar Warrier; Rahul Mohan; Manish Tiwari; Rajdeep Roy; Rajesh Asthana; Rasik Ravindra (Journal of Paleolimnology, 2017)

Phylogenetic analysis of Newcastle disease viruses from Bangladesh suggests continuing evolution of genotype XIII - Lalita Rani Barman; Mohammed Nooruzzaman; Rahul Deb Sarker; Md. Tazinur Rahman; Md. Rajib Bin Saife; Mohammad Giasuddin; Bidhan Chandra Das; Priya Mohan Das; Emdadul Haque Chowdhury; Mohammad Rafiqul Islam (Archives of Virology, 2017)

Spectrum of DNA variants for non-syndromic deafness in a large cohort from multiple continents - Denise Yan; Demet Tekin; Guney Bademci; Joseph Foster; F. Basak Cengiz; Abhiraami Kannan-Sundhari; Shengru Guo; Rahul Mittal; Bing Zou; Mhamed Grati; Rosemary I. Kabahuma; Mohan Kameswaran; et al. (Human Genetics, 2016)

Particulate and gaseous emissions in two coastal cities—Chennai and Vishakhapatnam, India - Sarath K. Guttikunda; Rahul Goel; Dinesh Mohan; Geetam Tiwari; Ravi Gadepalli (Air Quality, Atmosphere & Health, 2015)

Latitudinal shifts in the Polar Front in Indian sector of the Southern Ocean: evidences from silicoflagellate assemblage - Suhas S. Shetye; Rahul Mohan; Abhilash Nair (Geosciences Journal, 2014)

Contrasting productivity and redox potential in Arabian Sea and Bay of Bengal - Suhas S. Shetye; Maruthadu Sudhakar; Rahul Mohan; Babula Jena (Journal of Earth Science, 2014)

Provenance and temporal variability of ice rafted debris in the Indian sector of the Southern Ocean during the last 22,000 years - M C MANOJ; MELOTH THAMBAN; A SAHANA; RAHUL MOHAN; KOTHA MAHENDER (Journal of Earth System Science, 2013)

Evidence for climatic and oceanographic controls on terrigenous sediment supply to the Indian Ocean sector of the Southern Ocean over the past 63,000 years - Madhusudhanan C. Manoj; Meloth Thamban; Natani Basavaiah; Rahul Mohan (Geo-Marine Letters, 2012)

Complete nucleotide sequence of cherry virus A (CVA) infecting sweet cherry in India - M. S. Noorani; P. Awasthi; Rahul Mohan Singh; Raja Ram; M. P. Sharma; S. R. Singh; N. Ahmed; V. Hallan; A. A. Zaidi (Archives of Virology, 2010)

Guanidine hydrochloride and urea-induced unfolding of Brugia malayi hexokinase - Alok Ranjan Singh; Shweta Joshi; Rahul Arya; Arvind Mohan Kayastha; Jitendra Kumar Saxena (European Biophysics Journal, 2010)

Relative Microalgal Concentration in Prydz Bay, East Antarctica during Late Austral Summer, 2006 - Rahul Mohan; Sunil Kumar Shukla; N. Anilkumar; M. Sudhakar; Satya Prakash; R. Ramesh (Algae, 2009)

Coccolithophores from the central Arabian Sea: Sediment trap results - Lina P. Mergulhao; Rahul Mohan; V. S. N. Murty; M. V. S. Guptha; D. K. Sinha (Journal of Earth System Science, 2006)